(untitled) (Research, Society and Development, 2021)
This work is the result of a research carried out in the Licentiate Degree in Indigenous Teacher Training, Alto Rio Negro class, referring to the Teaching Internship developed in the Discipline of Stage III of the Exact and Biological Sciences Course. Thus, we aim to understand the challenges and learning made by the indigenous people during the Internship III course taught via TIC’s. This is an ethnographic research with a qualitative approach, in which we had five indigenous students in training as participants. For the collection of information, we carried out a participant observation using the Formative Path via Google Meet and WhatsApp. Data analysis was carried out through categories created from keywords. As for the results achieved, we highlight that, among the challenges, we can mention the difficulty of accessing the internet in remote communities in the interior of Amazonas. The learning constituted during the course is related to the construction of the Indigenous Didactic Instrument for the teaching of mathematics in the daily life of indigenous schools, raising the constitution of identity through the appreciation of the culture of indigenous peoples in formation, as well as the relationship between knowledge from academia and knowledge from tradition. Regarding the study, we concluded that, despite the difficulties faced, the Stage III discipline fostered reflections on the recognition of the living environment as a rich and conducive space for the production of didactic-pedagogical materials that can help in the teaching-learning process of Mathematics.